Configuring the field of global marine biodiversity conservation - Campbell, Lisa M.; Gruby, Rebecca; Gray, Noella J. (Frontiers in Marine Science, 2024)
Introduction The article describes and analyzes the emergence of the field of global marine biodiversity conservation over the past fifteen years. We draw on collaborative research at international meetings, which we position as ‘field’ sites, places where diverse actors come together to negotiate the meaning and terms of global environmental governance and where that work is accessible and visible to researchers. Methods Based on Collaborative Event Ethnography (CEE), a method developed to facilitate study of large meetings, we mobilize research from seven meetings since 2008 to describe the field of global marine biodiversity conservation, but more importantly to specifying how that field has been configured. Results We identify practices of orchestration, narrative, performance, alliance, social objects, devices, and technologies, formal outcomes, and formal procedures, and their use at three phases of field configuration: building, framing, and bounding. Discussion The results: 1) enhance our understanding of the role of international conferences in global environmental governance generally, and for marine biodiversity conservation specifically; 2) demonstrate the relevance of field and field configuration theory; 3) contribute to theory on institutional fields by specifying practices of field configuration.